PENGEMBANGAN BAHAN AJAR MENULIS BERBASIS NILAI-NILAI KEARIFAN LOKAL - Saputro, Edi (LPPM STKIP PGRI Bandar Lampung, 2015)
This study aims to produce teaching materials based writing the values of local wisdom to SMP Muhammadiyah 1 Tulang Bawang Tengah Grade VII Semester I. This study uses a model of Research and Development Research (DRD) with three main stages. 1) Preliminary study obtained preliminary information about the learning objective conditions, requirements, and principles of development of teaching materials based local wisdom values. 2) develop a preliminary design of products, peer assessment, testing experts, small-scale test, and large-scale test. Revised product development carried out by the inputs of each assessment or test performed. 3) The results of testing the effectiveness of the product in SMP Muhammadiyah 1 TBT showed enhancing the quality of learning outcomes, quality of learning, and the cultivation of character of local. Comparison of mean pretest and posttest scores showed obvious improvement, the analysis of the index shows a gain medium category. The findings in this study are useful for teachers, students, and SMP Muhammadiyah 1 TBT as a material consideration in the preparation of the next KTSP.